The economics of nestmate killing in avian brood parasites: A provisions trade-off - Gloag, Ros (2012)
Some brood parasites kill all their host's offspring shortly after hatching, whereas others are tolerant and are reared in mixed host-parasite broods. This difference may arise because nestling parasites face a "provisions trade-off," whereby the presence of host nestlings can increase or decrease a parasite's food intake depending on whether host young cause parents to supply more extra food than they consume. We model this trade-off and show that the optimal nestmate number from a parasite's perspective depends on the interaction of 2 parameters describing a parasite's stimulative and competitive properties, relative to host young. Where these parameters differ from one host-parasite pair to the next, either nestmate killing or nestmate tolerance can be favored by natural selection for maximum intake. We show that this extends to variation between hosts of generalist parasites. In an experimental field study, we found that nestling shiny cowbirds (Molothrus bonariensis) reared by house wrens (Troglodytes aedon) had higher food intake and mass growth rate when accompanied by host young than when alone, whereas those reared by chalk-browed mockingbirds (Mimus saturninus) had higher food intake, mass growth, and survival when reared alone than with host young. In both hosts, total provisioning was higher when host nestlings were present, but only in house wrens did cowbirds secure a sufficient share of that extra provisioning to benefit from host nestlings' presence. Thus, a provisions trade-off might generate opposing selective forces on the evolution of nestmate killing not only between parasite species but also within parasite species using multiple hosts.